Economía creativa, un modelo de desarrollo sostenible: una mirada desde la UNESCO - Valdivieso Arpi, Ritha Camila (2022)
The United Nations declared 2021 as the year of the "Creative Economy for Sustainable Development", understanding a tripartite approach to development, including economic, social, and environmental issues, and for it to last over time. UNESCO positions the creative economy within the international concert as an economic model that is not based on the exploitation of natural resources, but rather its way of doing economy is one of the most dynamic as it includes socio-cultural aspects and where its industries use creativity. , knowledge, culture and social innovation as an opportunity for developing countries and a development model for a sustainable future. The research presents a theoretical overview of the dimensions of the object of study: creative economy and related concepts that support the research. From a descriptive study, the method of documentary and content analysis is used. The value chain that makes up the creative industries as the heart of the creative economy is analyzed. The classification model for creative industries and the strategic dimensions of the creative